SOCIAL REHABILITATION AS ONE OF THE PROFESSIONAL ACTIVITIES OF A SOCIAL WORK SPECIALIST - Iryna V. Oliynik (Alfred Nobel University Publisher, 2021)
The article defines the main vector of the direction in professional training of future social workers. Definitions of the concepts of social rehabilitation and rehabilitation process are considered. The main aspects of social rehabilitation are disclosed. Based on the analysis of psychological, sociological, complex models of social and socially pedagogical work, models of social rehabilitation are identified: psychological, psychodynamic, behavioral, cognitive-behavioral, humanistic, existential, sociological. The most common approaches to the implementation of sociological models of rehabilitation for social work are analyzed: systemic, ecological, role-playing and radical. The general theoretical foundations of social rehabilitation are described as a component of social and pedagogical activity, their common goals are defined, namely, the preservation and support of the individual, the group in a state of active, creative, independent attitude towards itself, its life and activity. The peculiarities of the organization of social rehabilitation are outlined and the main characteristics of this process are determined. Firstly, this is a gradual solution of problems aimed at restoring the social status of an individual, forming resistance to traumatic situations, forming a person capable of successfully integrating into society. Secondly, social rehabilitation as an end result should be aimed at achieving the ultimate goal, when a person, after undergoing comprehensive rehabilitation, becomes immersed in the socio-economic life of society and feels integrated. Thirdly, social rehabilitation acts in the form of social technology, i.e. a certain way of implementing rehabilitation activities as a result of identifying individual operations placed in a certain relationship and sequence, choosing the most effective methods of influencing the client.